Reduction of chromano–piperidine-fused isoxazolidines: Tandem intramolecular rearrangements leading to 2-(methylamino)-4-oxo-N-phenyl-N-propyl-4H-chromene-3-carboxamide. Issue 25 (21st June 2017) - Singh, Gagandeep; Gupta, Naman; Gupta, Vivek; Ishar, Mohan Paul Singh
Graphical abstract: Highlights: Reductive cleavage of NO bond of isoxazolidines (3a –c ) has been attempted. Reductive NO bond cleavage followed by intra-molecular tandem rearrangements. Providing chromene-3-carboxamide (4 ) having potential medicinal significance. Plausible mechanistic rationale for the formation of compound4 is proffered. Abstract: Reductive ring opening of isoxazolidine moiety of chromano–piperidine-fused isoxazolidines (3a –c ) with HCOONH4 and 10% Pd/C in a mixture of solvents (THF/MeOH) at ambient temperature, affords novel 2-(methylamino)-4-oxo- N -phenyl- N -propyl-4 H -chromene-3-carboxamide (4 ), which is apparently derived from reductive NO bond cleavage followed by tandem intramolecular rearrangements. Plausible mechanistic rationale for the formation of compound4 is proffered.